Outcomes and impacts of transnational higher education: a systematic literature review focusing on host countries / Bobir Muratov and Majid Ghasemy - Muratov, Bobir; Ghasemy, Majid (Universiti Teknologi MARA, 2025)
The growth of transnational higher education (TNHE) in recent decades has attracted increasing scholarly attention. This paper systematically reviews existing research on TNHE’s outcomes and impacts on host countries by analysing the research performance landscape, identifying common methodologies and theories, and thematising key findings. A total of 35 publications from the Web of Science database for the period of 2003–2023 were selected for performance and qualitative review. The findings reveal a rising research field dominated by authors from TNHE-exporting Western countries, supported by educational organizations, along with a notable presence of scholars from TNHE-importing countries. Researchers primarily examined the perspectives of graduates, students, and administrators, and employed qualitative methods, and conceptual and theoretical frameworks derived from management, social sciences, and philosophy. TNHE’s academic, human resource, economic, social, and research outcomes and impacts on host countries were identified through thematic analysis. While this model of higher education provision has proven successful for some countries, uncertain global events pose ongoing challenges to TNHE’s future sustainability.